THE PIG SLAUGHTER TRADITION AS A SYMBOL OF LOCAL WISDOM IN THE MARIND TRIBE - Farida Nugrahaeni; Sudrajat Sudrajat; Raras Gistha Rosardi; Khoirul Khoirul (UIN Fatmawati Sukarno Bengkulu, 2026)
This study aims to analyze the meaning, implementation process, and values of local wisdom in the pig slaughter tradition among the Marind community in Merauke Regency. This study uses a qualitative approach with descriptive methods. Data were collected through semi-structured interviews, observation, and documentation. The results show that the pig slaughter tradition has multidimensional functions, namely as a symbol of gratitude, a means of strengthening social solidarity, and legitimacy in customary law, particularly in land release. This tradition also contains local wisdom values such as reciprocal cooperation, deliberation, and social division. The role of traditional leaders is very important in maintaining the sustainability of the tradition, while cultural inheritance is carried out informally through the involvement of the younger generation. This study confirms that the pig slaughter tradition is a form of local wisdom that is relevant in strengthening the cultural identity and social integration of indigenous communities amidst the current of modernization.